Upstream Binding of Idling RNA Polymerase Modulates Transcription Initiation from a Nearby Promoter - Gerganova, Veneta (J Biol Chem, 2015)
The bacterial gene regulatory regions often demonstrate distinctly organized arrays of RNA polymerase binding sites of ill-defined function. Previously we observed a module of closely spaced polymerase binding sites upstream of the canonical promoter of the Escherichia coli fis operon. FIS is an abundant nucleoid-associated protein involved in adjusting the chromosomal DNA topology to changing cellular physiology. Here we show that simultaneous binding of the polymerase at the canonical fis promoter and an upstream transcriptionally inactive site stabilizes a RNAP oligomeric complex in vitro. We further show that modulation of the upstream binding of RNA polymerase affects the fis promoter activity both in vivo and in vitro. The effect of the upstream RNA polymerase binding on the fis promoter activity depends on the spatial arrangement of polymerase binding sites and DNA supercoiling. Our data suggest that a specific DNA geometry of the nucleoprotein complex stabilized on concomitant binding of RNA polymerase molecules at the fis promoter and the upstream region acts as a topological device regulating the fis transcription. We propose that transcriptionally inactive RNA polymerase molecules can act as accessory factors regulating the transcription initiation from a nearby promoter.